Reconsidering the Freedom to Learn Curriculum in Indonesia: Paulo Freire’s Perspective - Yoyok Amirudin; Jakfar Shodiq; Muh Syamsul Arifin (Akademika, 2026)
The aim of this study is to analyze the implementation of the policy related to Freedom to Learn (Merdeka Belajar) Curriculum in Indonesia from the perspective of Paulo Freire’s thinking. This study uses a Systematic Literature Review (SLR) strategy as part of a qualitative methodology. This strategy was used in order to obtain a thorough and in-depth comprehension of the study findings, methodology, and trends published between 2019 and 2025, I collected the documents consist of papers, books, and the policy from Ministry of Education and culture Indonesia and analyze it. The result of this study is freedom to learn curriculum some area adopted the Freire’s ide. The most prominent in this new concept is freedom, means students free to search any resource for increase their skill and competences. Freire’s argued students and teachers need dialogues in the learning process, he was criticism the banking education. Education was not like banking system that students only receipt the material and tested in the end of examination by memorizing. This study perhaps contributes to the advancement of Indonesian education and evaluate the freedom to learn curriculum.